Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/microorganisms10040722
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Isolates from COVID-19 Patients in a Hospital Intensive Care Unit: Molecular Typing and Risk Factors

Abstract: Infections caused by Acinetobacter baumannii represent a major concern for intensive care unit (ICU) patients. However, the epidemiology of these infections among COVID-19 patients has not been fully explored. The aims of this study were (i) to characterize the clonal spread of A. baumannii among COVID-19 patients admitted to the ICU of the Umberto I hospital of Rome during the first year of the pandemic and (ii) to identify risk factors for its acquisition. Isolates were analysed by pulsed-field gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 47 publications
1
30
2
Order By: Relevance
“…Our meta-analysis included nine el-igible studies in the field plus the current study (total of ten studies) (23)(24)(25)(26)(27)(28)(29)(30)(31) after an electronic search and removing duplicate and irrelevant records. The distribution of each survey by country is as follows: Spain, USA, Iran, Saudi Arabia, UK, Italy, a multicenter study from Italy, Croatia, Serbia, Slovenia, and two studies from Turkey.…”
Section: Meta-analysismentioning
confidence: 99%
“…Our meta-analysis included nine el-igible studies in the field plus the current study (total of ten studies) (23)(24)(25)(26)(27)(28)(29)(30)(31) after an electronic search and removing duplicate and irrelevant records. The distribution of each survey by country is as follows: Spain, USA, Iran, Saudi Arabia, UK, Italy, a multicenter study from Italy, Croatia, Serbia, Slovenia, and two studies from Turkey.…”
Section: Meta-analysismentioning
confidence: 99%
“…A recent study by Ceparano et al identi ed carbapenem exposure but not cephalosporin exposure as a risk factor for A. baumannii isolation in COVID-19 ICU patients. However, in their study carbapenem exposure was much more frequent than cephalosporin exposure, a factor that might have contributed to the results [27].…”
Section: Acinetobacter Superinfection In Covid-19 Patients and Antibi...mentioning
confidence: 85%
“…Previous studies have found that risk of MDR isolation in COVID-19 patients is associated with broad-spectrum antibiotics like piperacillin-tazobactam and carbapenems, but not with narrower spectrum antibiotics like cephalosporins and aminopenicillins. [26,27]. We identi ed ceftriaxone as an independent and potent risk factor for MDR-Ab superinfection in the setting of COVID-19 ICU patients.…”
Section: Clinical Relevance and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the emergence of SARS-CoV-2 in 2019, numerous studies have been reported worldwide with a high incidence of carbapenem-resistant A. baumannii among the COVID-19 patients admitted to ICUs [ 6 ]. In the ICU, Acinetobacter baumannii has been reported as one of the most common bacteria responsible for severe hospital-acquired infection, with a high mortality rate ranging from 45% to over 80% when the causative infectious agent is extensively drug-resistant (XDR) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%